중⋅장년층의 양대구강병 예방 지식이 올바른 구강위생용품사용과 구강병 예방실천에 미치는 영향 - 엄숙(Suk Eom); 최유진(Yu-Jin Choi); 권수진(Su-Jin Kwon) (한국구강보건과학회지, 2021)
Objectives: This study aims to understand the effects of preventive knowledge about two major oral diseases on the correct use of oral hygiene products and oral disease preventive practice of middle-aged class. Methods: This study conducted a survey targeting the middle-aged adults in 40-65, residing in Y region of Gyeongnam, and total 294 questionnaires were finally analyzed. Results: The results of two variables such as educational experience of oral disease(p<.05) and knowledge about periodontal disease(p<.01) had significant effects on the correct use of oral hygiene products. Such variables like sex(p<.05), age(p<.01), educational experience of oral health(p<.001), and knowledge about periodontal disease(p<.01) had significant effects on the oral disease preventive practice. Conclusions: Based on such results of this study, it would be necessary to vitalize the relevant researches in various perspectives. KCI Citation Count: 5